2018
DOI: 10.1002/ejlt.201800208
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Gamma‐Linolenic and Stearidonic Acids as Free Fatty Acids and Ethyl Esters from Viper's Bugloss Seed Oil by Urea Complexation

Abstract: In this work, gamma‐linolenic acid (GLA) and stearidonic acid (SDA) are successfully concentrated as free fatty acids (FFA) and ethyl esters (EE) using the urea complexation method at room temperature and two sources of these fatty acids: commercial Echium plantagineum seed oil as well as extracted oil from this species which is grown in Chile. Concentration factors (% fatty acid in the concentrate/% fatty acid in the original oil) for both fatty acids are found to be between 2.35 and 2.65, although they are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…Considering that the polarity of ethanol is slightly higher than that of 2-propanol, the higher yields of TPC and ORAC associated with the use of ethanol in the Randall mode suggest that the phenolic compounds which are susceptible to be extracted from the E. plantagineum seeds have a high polarity. The fact that solvents with high polarity are more efficient to extract polyphenols is in agreement with previous evidence showing that alcohols are more suitable solvents than nonpolar solvents such as n-hexane for polyphenol extraction from plant material (Roby et al, 2013), and that among alcohols, those with a higher relative polarity such as methanol (relative polarity = 0.762) are more efficient than those with a lower relative polarity such as ethanol (relative polarity = 0.654) (Reichardt and Welton, 2010) (Roby et al, 2013). However, ethanol is more suitable than methanol to be used in the food industry.…”
Section: Total Phenolic Content and Oracsupporting
confidence: 90%
See 1 more Smart Citation
“…Considering that the polarity of ethanol is slightly higher than that of 2-propanol, the higher yields of TPC and ORAC associated with the use of ethanol in the Randall mode suggest that the phenolic compounds which are susceptible to be extracted from the E. plantagineum seeds have a high polarity. The fact that solvents with high polarity are more efficient to extract polyphenols is in agreement with previous evidence showing that alcohols are more suitable solvents than nonpolar solvents such as n-hexane for polyphenol extraction from plant material (Roby et al, 2013), and that among alcohols, those with a higher relative polarity such as methanol (relative polarity = 0.762) are more efficient than those with a lower relative polarity such as ethanol (relative polarity = 0.654) (Reichardt and Welton, 2010) (Roby et al, 2013). However, ethanol is more suitable than methanol to be used in the food industry.…”
Section: Total Phenolic Content and Oracsupporting
confidence: 90%
“…FAME were identified according to their respective retention times compared with a mix of analytical standards (37 components FAME Mix from Supelco, Sigma‐Aldrich, St. Louis, MO, USA). FAME which were not available in the mix of standards, such as SDA, were identified after derivatization and GC injection of a commercial E. plantagineum seed oil (15200 NEWmega Echium oil from DeWit Specialty Oils, Texel, The Netherlands) whose fatty acid profile is known (Rincón‐Cervera et al, ). Analyses were carried out by triplicate and results are reported as mean value ± SD.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the energy consumption, we selected 25°C as the crystallization temperature. Crystallization at room temperature (20°C) was also used for the enrichment of γ‐linolenic acid from bugloss seed oil (Rincón‐Cervera, Galleguillos‐Fernández, González‐Barriga, Valenzuela, & Valenzuela, ). Different results were reported by Crexi, who chosen crystallization at −10°C for the separation of PUFA from carp oil (Crexi, Monte, Monte, & Pinto, ).…”
Section: Resultsmentioning
confidence: 99%
“…2(c)]. A few species are known to contain this fatty acid, but most of them are not crops, 81 and purple viper's bugloss is a commercial source of steridonic acid 29,81 . In Chile, it has recently been studied as a source of industrial oil 30,82 …”
Section: Industrial Oilseed Cropsmentioning
confidence: 99%
“…In contrast, the contents of bioactive compounds (phytoesterols and phenolics) were significantly higher when ethanol was used as a solvent in Randall method extraction 30 . Nevertheless, γ ‐linolenic and stearidonic acids are the most important products obtained from purple viper's bugloss oil; hence, the concentration of these fatty acids in purple viper's bugloss oil was evaluated via urea complexation 29 . The authors concentrated both fatty acids (2.5 and 2.6 times for γ ‐linolenic and stearidonic acids, respectively) as free fatty acids and ethyl esters and concluded that they were more efficiently concentrated as free fatty acids because of their potential as a functional ingredient 29 …”
Section: Industrial Oilseed Cropsmentioning
confidence: 99%